Efficacy of Eleusine coracana (L.) Gaertn (Ragi) husk for adsorption of chromium(VI): A study using response surface methodology. Issue 1 (1st April 2014) - Premkumar, M.; Abinandan, S.; Sowmya, V.; Shanthakumar, S.
<x xml:space="preserve">Abstract</x> In this study, the removal of hexavalent chromium from aqueous solution using ragi husk, an agricultural waste, has been reported. Response surface methodology was applied to statistically optimize the process variables such as pH (2–4), adsorbent dosage (2–5 g/L), initial chromium concentration (50–150 mg/L), rotating speed (50–100 rpm), and temperature (25–30°C) using the main effect plot and central composite design. A maximum removal of 68.64% of Cr(VI) was achieved under the optimum conditions of pH 2, adsorbent dose 2 g/L, initial chromium concentration 150 mg/L, rotating speed 100 rpm, and temperature 30°C. The statistical analysis of the data shows that the experiments are statistically significant with a regression coefficient (R2) value of 0.9445. The surface morphology of the adsorbent was elucidated using scanning electron microscopy, and the functional groups present in the adsorbent that aids in the removal of Cr(VI) were identified using Fourier transform infrared spectroscopy. The experimental results revealed that ragi husk can be used as a potential adsorbent for the removal of hexavalent chromium from aqueous solution. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 139–145, 2015